Fantastic voyage: the journey of intestinal microbiota-derived microvesicles through the body. (19th October 2018) - Stentz, Régis; Carvalho, Ana L.; Jones, Emily J.; Carding, Simon R.
Abstract : As part of their life cycle, Gram-negative bacteria produce and release microvesicles (outer membrane vesicles, OMVs) consisting of spherical protrusions of the outer membrane that encapsulate periplasmic contents. OMVs produced by commensal bacteria in the gastrointestinal (GI) tract of animals are dispersed within the gut lumen with their cargo and enzymes being distributed across and throughout the GI tract. Their ultimate destination and fate is unclear although they can interact with and cross the intestinal epithelium using different entry pathways and access underlying immune cells in the lamina propria. OMVs have also been found in the bloodstream from which they can access various tissues and possibly the brain. The nanosize and non-replicative status of OMVs together with their resistance to enzyme degradation and low pH, alongside their ability to interact with the host, make them ideal candidates for delivering biologics to mucosal sites, such as the GI and the respiratory tract. In this mini-review, we discuss the fate of OMVs produced in the GI tract of animals with a focus on vesicles released by Bacteroides species and the use of OMVs as vaccine delivery vehicles and other potential applications.